Zastosowanie rozwiązań informatycznych w organizacji sieciowej na przykładzie PEKAES Multi-Spedytor - Kołoszycz, Ewa; Kołoszycz, Mieczysław (Applications of Information Technology in Network Organization - Case of PEKAES Multi-Spedytor, 2005)
In publication the implementation of computer system was shown. As the example the PEKAES Multi-Spedytor Ltd. was used. General structure, operation and advantages of implementation were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 324-327